A new translation of Shakespeare’s Richard II: the motivation for the project - I. O. Shaytanov (Шаги)
The article introduces ongoing work on a new translation of Shakespeare’s Richard II, and sets out the motivation for this undertaking. This chronicle, the first in the cycle of Shakespeare’s history plays known as the second tetralogy, was written in 1595 when London theatres opened after a two-year pause due to the disastrous plague. Known primarily for its thematic actuality, King Richard dethroned, the play has been appreciated for its new reflexivity, manifested in the metaphysical style associated with John Donne but first introduced in Shakespeare’s work. Of the two major stylistic planes in Richard II, the “metaphysical” one has proved to be the most baffling for Russian translators, all of whom worked on the play before the decisive turn towards a metaphysical style in Russian verse accomplished by Joseph Brodsky, who was impressed by the English poets and later incorporated it in his individual style. The verbal fluency of the rhetoric of the royal chambers also is not adequately conveyed in the older Russian versions of the play. The manner of the four former translators — Nikolai Kholodkovsky (1902), Modest Chaikovsky (1906), Anna Kurosheva (1934), and Mikhail Donskoy (1958) — is illustrated and analyzed in their stylistic work in the scene (I, 3) when Richard II comes down from his throne to greet his cousin the Duke of Hereford (Bolingbroke). A number of other passages from the first two acts are presented and discussed. To make up for the inadequacy in the major styles of the play a new translation has been undertaken.